Effects of residual stress on the mechanical properties of copper processed using ultrasonic-nanocrystalline surface modification - Ji Hyun Moon; Seung Mi Baek; Seok Gyu Lee; Yujin Seong; Auezhan Amanov; Sunghak Lee; Hyoung Seop Kim (Materials Research Letters, 2019)
Effects of surface grain refinement and residual stress on the local and global properties of pure Cu processed using ultrasonic nanocrystalline surface modification (UNSM) was investigated. To distinguish each contribution to the local hardness and global tensile properties of the UNSM treated Cu, a stress-relief specimen of the same microstructure as the UNSM treated one was produced by low-temperature annealing after the UNSM treatment. The distinct contributions of residual stress and surface grain refinement to the tensile property of UNSM treated Cu were determined and discussed.